DESCRIPTION OF A NEW SAN LUIS POTOSIECIES AND A NEW SUBSAN LUIS POTOSIECIES OF ENTOCYTHERE - RIOJA, ENRIQUE (Rockefeller Foundation, CD MEXICO, DF, MEX, 1944)
Glossosiphonia conchata is described For many species new areas of distribution are given, and for others new morph data
CIENC MEX
Keywords: DESCRIPTION, NEW SPECIES, NEW SUBSPECIES, ENTOCYTHERE; MULTIDISCIPLINARIA; BIOLOGIA VEGETAL; BOTANICA GENERAL